Mustia hilachosa del frijol y su control - Galvez, G.; Franco, T.; Mora, B.; Rojas, M. (Centro Internacional de Agricultura Tropical (CIAT), Centro de Informacion sobre Frijol-Patologia, 1987)
The symptomatology, biological cycle, epidemiology, and var., cultural, chemical, and integrated control of web blight of beans (Thanatephorus cucumeris) are briefly analyzed. Color photos are included. (CIAT)